Linking neuropolitics to the politics of reconciliation in relation to political non-apology: a case of Malaysia / Rugayah Hashim, Mohd Anuar Mazuki and Mohd Faiz Ismail - Hashim, Rugayah; Mazuki, Mohd Anuar; Ismail, Mohd Faiz (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The theory of neuropolitics emerged from that of neuroscience or brain science. In linking this theory to politics, the fundamental study was undertaken to provide insights on the factors for non-apologetic behavior among politicians. During public debates, it is the politician's responsibility to ensure factual accuracies to avoid controversies and backlashes. The implications of inaccuracies would affect the faith and image of the politician in the eyes of the constituent that they represent. As a public figure, any unwarranted actions are food for the paparazzi's and news travel fast aided by information and communication technologies. Saying sorry in public is not a strong forte of most politicians but failure to apologize will also result in suffrage.